Environmental sustainability assessment method for Moroccan residential buildings - Redouan Assadiki; Gérard Merlin; Catherine Buhé; Hervé Boileau; Fouzi Belmir (MethodsX)
The method presented in this paper provides for the deployment of a sustainability assessment of residential buildings in local contexts in Morocco. The main purpose is to develop a description sheet for each criterion for 29 subcategories of the “Moroccan Building Sustainability Assessment Framework,” environmental dimension (MBSAF(Env)). Firstly, a set of indicators with possible measures was identified; then, we reviewed national standards and existing green building rating systems. Then, several discussions involving a panel of experts (e.g., engineers, academics) were conducted to consolidate the threshold assessment. The main purpose is scored using a rating scale-based sustainability assessment procedure that is specifically designed for the assessment of new and existing Moroccan residential buildings. • MBSAF(Env) consoled risk management and adaptation of climate change indicators. • The framework provides an adaptability for new and existing residential buildings, taking the regionalization contexts of Morocco. • All criteria and indicator ratings are represented within a −1 to 5-point scale, and their thresholds are identified by national and international standards.